Weiterbildung "Individuelle Förderung in der beruflichen Bildung" - Entwicklungen und Implementation eines Blended Learning Ansatzes im Projekt InLab - Kremer, H.-Hugo; Rhode, S.; Zoyke, A. (Individuelle Förderung und berufliche Orientierung im berufsschulischen Übergangssystem - Ergebnisse aus dem Forschungs- und Entwicklungsprojekt InLab)

Stärkenbasierte Bildungsarbeit zur individuellen Kompetenzentwicklung im Übergang von Schule zu Berufs- und Arbeitswelt - Kremer, H.-Hugo; Knust, S. (Individuelle Förderung und berufliche Orientierung im berufsschulischen Übergangssystem - Ergebnisse aus dem Forschungs- und Entwicklungsprojekt InLab)

Berufsorientierung als Herausforderung für berufsbildende Schulen - Kremer, H.-Hugo (Die berufsbildende Schule)

Didaktische Potenziale des Mobile Learning für die Berufsbildung: Erfahrungen aus einem Pilotprojekt am Center for Young Professionals in Banking in der Schweiz - Seufert, Sabine; Jenert, Tobias; Kuhn-Senn, Andrea (Berufsbildung in Wissenschaft und Praxis)
Mobile Learning liegt in der beruflichen Bildung seit dem Aufkommen von Smartphones, Tablet-PCs1 und speziell entwickelten Applikationen (Mobile Apps) im Trend. Ziel des Beitrags ist es, die didaktischen Potenziale des Mobile Learning durch den Einsatz von Tablet-PCs in der beruflichen Ausbildung zu untersuchen. Als Ausgangspunkt dient dabei das Fallbeispiel des Center for Young Professionals in Banking in der Schweiz, das im Jahr 2011 eine umfassende Pilotstudie durchgeführt hat. Ausgehend vom konkreten Fall werden anschliessend die Potenziale für medienbezogene Kompetenzen sowie eine "didaktische Landkarte" zur Verortung von Mobile-Learning-Szenarien eingeführt, um die verschiedenen pädagogischen Leitvorstellungen dieser Szenarien aufzuzeigen.
Keywords: mobile learning; tablets; tablet learning; mobile technologies; elearning; TEL

Studienprogramme als didaktische Gestaltungs-und Untersuchungseinheit: Theoretische Grundlegung und empirische Analyse - Jenert, Tobias
Mit welchen Erwartungen und Anforderungen sehen sich Studierende im Hochschulalltag konfrontiert? Wie muss nach Ansicht der Studierenden gehandelt werden, um das Studium "erfolgreich" zu bewältigen? Wie laufen die Auswahl unterschiedlicher Lernaktivitäten im Studium sowie die Allokation von Ressourcen im Detail ab? Diese und weitere Fragen sind vor allem im Zusammenhang mit der Debatte um die Bologna-Reform stärker in den Mittelpunkt gerückt. Denn während modularisierte Curricula und Credit-Point-Systeme oft nach administrativ-organisatorischen Gesichtspunkten eingeführt wurden, hat die Gestaltung der Studienstrukturen auf Programmebene zwangsweise Auswirkungen auf das Studienhandeln - und damit auch auf das Lernen der Studierenden. Es gibt viele Vermutungen über die "Wirkungen" von Bologna auf das Studieren: Die Rede ist von Verschulung, Entwissenschaftlichung und Arbeitsüberlastung und Studierende stehen im Verdacht, ihren Studienpfad eher im Sinne einer Credit-Point-Jagd denn interessengeleitet zu gestalten. In der Regel bleibt es dabei jedoch bei anekdotischen Beobachtungen - es fehlt bislang an gesicherten Erkenntnissen über Zusammenhänge zwischen Bologna-konformen Studienkontexten und dem Handeln Studierender. Denn obschon Studierende seit langem Gegenstand der Forschung sind, ist bislang wenig darüber bekannt, wie sie den langfristigen Bildungsprozess eines ganzen Studiums gestalten. Stattdessen wurde vorwiegend das Lernen im engeren Sinne, das so genannte "Classroom Learning" untersucht. Diejenigen, die Studienprogramme nach didaktischen Gesichtspunkten gestalten wollen müssen wissen, wie Studierende mit unterschiedlichen Studienstrukturen umgehen. Denn nur so ist eine planvolle Programmgestaltung im Sinne pädagogischer Zielsetzungen und didaktischer Prinzipien möglich. Die vorliegende Arbeit nimmt diese Problemstellung auf und untersucht, welche Zielvorstellungen und Handlungsstrategien Studierende bei der Bewältigung ihres Studienalltags in unterschiedlichen Bologna-konformen Studienprogrammen entwickeln. Im Einzelnen wird gefragt, (1) welche Vorstellungen, Wahrnehmungen und Handlungslogiken das Handeln Studierender in unterschiedlichen Studienprogrammen prägen und (2) welche programmspezifischen Kontextbedingungen die Herausbildung dieser handlungsleitenden Charakteristika beeinflussen. Ausgehend von diesen beiden Fragestellungen wird zunächst ein theoretisch fundierter Analyserahmen für Studienprogramme entwickelt. Darauf aufbauend werden verschiedene Studienprogramme empirisch untersucht, um schliesslich Design-Prinzipien für die Gestaltung von Studienprogrammen zu formulieren. Es wird nicht davon ausgegangen, dass Studienstrukturen das Handeln Studierender im Sinne eines kausalen Wirkungszusammenhangs bestimmen. Vielmehr wird gefragt, was die Studierenden mit den Strukturen, auf die sie treffen, machen. Studienprogramme werden als kulturelle Einheiten verstanden, innerhalb derer sich spezifische handlungsleitende Vorstellungen und Normen entwickeln. Diese impliziten Regeln des Studienhandelns - das so genannte "Hidden Curriculum" - und vor allem auch die dahinterliegenden Konstruktionsprozesse aufzudecken, ist Ziel dieser Arbeit.
Keywords: Studierverhalten; Hochschuldidaktik; Lernpsychologie; Kulturpsychologie; Bologna-Prozess; Curriculumentwicklung; Hochschulbildung; Study programme; Bologna-process; educational development; cultural psychology; higher education; curriculum development

Status Quo von Hochschuldidaktik/-entwicklung: Erhebung im Herbst 2011 - Brahm, Taiga; Jenert, Tobias
Keywords: Hochschulentwicklung; Hochschuldidaktik

Studienprogramme als hochschuldidaktische Gestaltungs-und Untersuchungseinheit - Jenert, Tobias
In den vergangenen Jahren wurden viele Vermutungen über die "Wirkungen" von Bologna auf das Studieren geäussert: Schlagworte wie Verschulung oder Entwissenschaftlichung sind zu hören und Studierende stehen im Verdacht, ihr Studium eher als Credit-Point-Jagd denn interessengeleitet zu gestalten (z.B. Stegemann, 2007, o. S.; Schultheis, et al. 2008). Meist handelt es sich jedoch um anekdotischen Beschreibungen, bis auf wenige Ausnahmen fehlen empirisch belegte Erkenntnisse.1 Denn obschon Studierende seit langem Gegenstand der Forschung sind, ist bislang wenig darüber bekannt, wie sie den langfristigen Bildungsprozess eines ganzen Studiums gestalten. Vorwiegend wurde Lernen im engeren Sinne, das so genannte "Classroom Learning" untersucht (Aineley, 2008). Forschungsfokus. Die diesem Beitrag zugrunde liegende Studie nimmt diese Forschungslücke auf und untersucht Zielvorstellungen und Handlungsstrategien Studierender bei der Bewältigung ihres Studienalltags in unterschiedlichen Bologna-konformen Studienprogrammen. Im Einzelnen wird gefragt, (1) welche Vorstellungen und Wahrnehmungen das Handeln Studierender prägen und (2) welche programmspezifischen Kontextbedingungen die Herausbildung dieser handlungsleitenden Charakteristika beeinflussen. Als theoretischer Rahmen wurde die so genannte Kulturpsychologie herangezogen, die Handeln als Resultat einer Wechselwirkung von individuell-psychischen Merk-malen und sozio-kulturell vermittelten Vorstellungen versteht (Shweder, 1991; Bruner, 1990).
Keywords: Hochschulentwicklung; Studienprogramme; Curriculum Development; Higher Education; Faculty Development

" Nur" didaktisch oder auch strategisch?: Strukturelle Verankerung, Aufgaben-und Wirksamkeitswahrnehmungen hochschuldidaktischer Einrichtungen in Deutschland - Jenert, Tobias; Brahm, Taiga
Die Lehrpraxis an Hochschulen breitenwirksam und nachhaltig zu verbessern, gehört zu den schwierigsten Herausforderungen für die Hochschuldidaktik. Ein möglicher Weg besteht darin, als hochschuldidaktische Einrichtung stets mit Blick auf die Gesamtstrategie der Hochschule und Anspruchsgruppen in der Hochschulleitung und -administration zu agieren (Jenert & Brahm, 2010). Es stellt sich die Frage, welche Vorstellungen bezüglich der eigenen Aufgaben und der Wirksamkeit des eigenen Handels hochschuldidaktische Stellen in Deutschland haben. Mit einer Online-Befragung von Leitungspersonen im Bereich Hochschuldidaktik und -entwicklung in Deutschland konnten 35 Personen (72 angeschrieben) erreicht werden, wobei sich ein breiter Querschnitt verschiedener Einrichtungen ergab. Abgefragt wurden (1) Struktur und institutionelle Anbindung der Einrichtung, (2) Wahrnehmung der eigenen Wirksamkeit sowie (3) Aufgabenschwerpunkte und notwendige Kompetenzen. Die Ergebnisse zeigen, dass einerseits ein Bewusstsein für Herausforderungen jenseits didaktischer Aus- und Weiterbildung besteht und die strategische Dimension erkannt ist. Gleichzeitig zeigt die Betonung "traditioneller" Aufgaben und Kompetenzen, dass die strategische Dimension im Tagesgeschäft oft noch keine zentrale Rolle spielt.
Keywords: Hochschulentwicklung; higher education development; Hochschuldidaktik

How to Assess and Study the Cultural Dimension of Social Interactions in Higher Education Institutions (HEI) - Gebhardt, Anja; Jenert, Tobias
Keywords: learning culture; social interaction

Institutionsweite Hochschulentwicklung als neo-institutionalistisches Phänomen - Brahm, Taiga; Gerholz, Karl-Heinz; Jenert, Tobias
Hintergrund / Kontext In der Hochschuldidaktik hat sich der traditionelle Ansatz, der sich auf das Individuum bezogene Aus- und Weiterbildungs- sowie Beratungsangebote konzentriert, weitgehend etabliert (Urban & Meister, 2010; Land, 2010; Dany, 2007). Allerdings sind diese Aktivitäten in Bezug auf die Bildungsqualität einer gesamten Hochschule oft wenig wirksam. Der Ansatz schlägt vor, hochschuldidaktische Initiativen auf mehreren Ebenen der Hochschule zu verankern: individuelle, programmbezogene und institutionelle Massnahmen (Jenert & Brahm, 2010; Brahm et al., 2010). Zielsetzung / Fragestellung Der Ansatz einer institutionsweiten Hochschulentwicklung wird vor dem Hintergrund einer aktuellen Erhebung zum Status Quo der Hochschuldidaktik diskutiert. Im Zentrum steht die Frage, wie, didaktische Initiativen in der Hochschule nachhaltig verankert werden können. Untersuchungsdesign / Datenerhebung und -auswertung In einer Online-Befragung wurden 32 Hochschuldidaktiker aus Deutschland und der Schweiz befragt. Zur Vertiefung wurden fünf telefonische Interviews durchgeführt. Die schriftlichen Befragungsdaten wurden mittels SPSS, die Interviews (nach der Transkription) inhaltsanalytisch ausgewertet. Erste Ergebnisse Die meisten hochschuldidaktischen Einrichtungen konzentrieren sich auf die Organisation und Durchführung von Qualifizierungsmassnahmen (für 71,9% der Befragten gehört dies zu den bedeutsamen Aufgaben). Dagegen wird die Unterstützung von Programmverantwortlichen oder der Hochschulleitung nur von einem Viertel der Befragten als wichtige Aufgabe erachtet. In den Interviews wird deutlich, dass nur wenige Ansätze bestehen, wie didaktische Initiativen in die gesamte Hochschule getragen werden können. Berufs- und wirtschaftspädagogische Relevanz Die ersten Ergebnisse der Untersuchung zeigen, dass das Feld der Hochschuldidaktik und -entwicklung bisher noch wenig strukturiert ist. Bestehende Ansätze der Berufs- und Wirtschaftspädagogik (z. B. Euler & Sloane, 1999; Gerholz et al., 2010; Gerholz, 2012) können einen Beitrag dazu leisten, didaktische Veränderungsinitiativen innerhalb der Hochschulen wirksamer und nachhaltiger zu gestalten.
Keywords: Hochschuldidaktik; Hochschulentwicklung; Neo-Institutionalismus; Strategie

Programmgestaltung als professionelle Aufgabe der Hochschulentwicklung: Gestaltungsmodell und Fallstudie - Jenert, Tobias (Einführung in die Studiengangentwicklung)

Studierende (als) Kunden?: Zum Umgang mit einer herausfordernden Beziehung zwischen Lehrenden und Lernenden - Jenert, Tobias; Fust, Alexander (Lernendenorientierung: Studierende im Fokus)

Service - Forscher - Change Agents?! Rollen und Strategien einer gestaltungsorientierten Hochschulentwicklung: Keynote-Vortrag im Rahmen des Jungen Forums Hochschul-und Mediendidaktik - Jenert, Tobias

An iterative plug-in algorithm for decomposing seasonal time series using the Berlin Method - Feng, Yuanhua (Journal of Applied Statistics)

Optimal convergence rates in non-parametric regression with fractional time series errors - Feng, Yuanhua; Beran, Jan (Journal of Time Series Analysis)

Filtered Log-Periodogram Regression of Long Memory Processes - Feng, Yuanhua; Beran, Jan (Journal of Statistical Theory and Practice)

Weighted Averages and Local Polynomial Estimation for Fractional Linear ARCH Processes - Beran, Jan; Feng, Yuanhua (Journal of Statistical Theory and Practice)

Weighted Averages and Local Polynomial Estimation for Fractional Linear ARCH Processes - Beran, Jan; Feng, Yuanhua (Journal of Statistical Theory and Practice)

Locally Weighted Autoregression - Feng, Yuanhua; Heiler, Siegfried (Econometrics in Theory and Practice)

A Multivariate Random Walk Model with Slowly Changing Drift and Cross-correlation Applied to Finance - Feng, Yuanhua; Hand, David; Yu, Keming

The demand for individual grievance procedures in Germany and Spain: Labour law changes versus business cycle - Frick, Bernd; Ocaña, Miguel Ángel Malo; Martinez, Pilar Garcia; Schneider, Martin (Estudios de economia aplicada)

Who owns the customer? Disentangling customer loyalty in indirect distribution channels - Eggert, Andreas; Henseler, J{\; Hollmann, Sabine (Journal of Supply Chain Management)

‘It's almost like taking the sales out of selling’—towards a conceptualization of value-based selling in business markets - Terho, Harri; Haas, Alexander; Eggert, Andreas; Ulaga, Wolfgang (Industrial Marketing Management)

Individuelle Förderung und berufliche Orientierung im berufsschulischen Übergangssystem - Ergebnisse aus dem Forschungs- und Entwicklungsprojekt InLab

Funktionen und Erträge pädagogischer Diagnostik im wirtschafts- und berufspädagogischen Bereich - Tramm, T.; Seeber, S.; Kremer, H.-Hugo (bwp@ Berufs- und Wirtschaftspädagogik - online)

Akademisierung der Berufsbildung - Büchter, K.; Frommeberger, D.; Kremer, H.-Hugo (bwp@ Berufs- und Wirtschaftspädagogik - online)

Vorstellung des Modellprojekts InLab - Beutner, Marc; Kremer, H.-Hugo; Zoyke, A (Individuelle Förderung und berufliche Orientierung im berufsschulischen Übergangssystem. Ergebnisse aus dem Forschungs- und Entwicklungsprojekt InLab)

Vorstellung von vier Instrumenten zur Individuellen Förderung - Beutner, Marc; Frehe, Petra; Gebbe, M; Gockel, C; Kremer, H.-Hugo; Zoyke, A (Individuelle Förderung und berufliche Orientierung im berufsschulischen Übergangssystem. Ergebnisse aus dem Forschungs- und Entwicklungsprojekt InLab)

A Method for Selectively Designing Modeling Languages for Product-Service Systems - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf (Modeling for Decision Support in Network-Based Services: The Application of Quantitative Modeling to Service Science)

Ansätze zur methodischen Unterstützung der Konstruktion von Produktivitätsmodellen für die Data Envelopment Analysis --- Entwicklung eines Softwareprototypen zur Umsetzung und Evaluation - Becker, Jörg; Knackstedt, Ralf; Beverungen, Daniel; Dietrich, Hanns-Alexander; Breuker, Dominic; Peter Rauer, Hans (Service Engineering --- Management)

Product-Service System Approaches - Beverungen, Daniel; Matzner, Martin; Müller, Oliver; Becker, Jörg (Handbook of Service Description)

Besteuerung von Beteiligungsinvestitionen und Risikoempfindlichkeit – Wie wirkt die Abgeltungssteuer? - Hegemann, Annika

Asymmetric Taxation of Profits and Losses and Its Influence on Investment Timing: Paradoxical Effects of Tax Increases - Mehrmann, Annika; Schneider, Georg; Sureth-Sloane, Caren

Mehr Theorie wagen. Betriebswirtschaftslehre nach Bologna oder Hochschulbildung im Wandel - Sloane, Peter F. E.; Sureth-Sloane, Caren (Wirtschaft und Beruf)

Analytisch und strukturiert denken lernen - Sureth-Sloane, Caren (Frankfurter Allgemeine Zeitung)

Studium nach Bologna: Theorie oder Praxis – ein Scheinwiderspruch? - Sureth-Sloane, Caren (Frankfurter Allgemeine Zeitung)

Unternehmensführung und interkulturelle Hochschulbildung. Unternehmensführung in Europa - Interkulturelle Fragen - Sureth-Sloane, Caren (Wirtschaft und Beruf)

Vorwort. Geschichte des VHB und der BWL: Rückblick und Einblicke - Sureth-Sloane, Caren (Der Verband der Hochschullehrer für Betriebswirtschaft, Geschichte des VHB und Geschichten zum VHB)

Welcher BWLer ist ein guter Forscher? - Sureth-Sloane, Caren; zu Knyphausen-Aufseß, Dodo (Frankfurter Allgemeine Zeitung)

Die Prinzipal-Agent-Theorie als Erklärungsinstrumentarium von Korruption - Gilroy, Bernard Michael; Kruse, Daniel (WiSt-Wirtschaftswissenschaftliches Studium)

To buy or not to buy? The value of contradictory analyst signals - Kanne, Stefan; Klobucnik, Jan; Kreutzmann, Daniel; Sievers, Sönke (Financial Markets and Portfolio Management (VHB-JOURQUAL 3 Ranking C))
We study the predictive ability of individual analyst target price changes for post-event abnormal stock returns within each recommendation category. Although prior studies generally demonstrate the investment value of target prices, we find that target price changes do not cause abnormal returns within each recommendation level. Instead, contradictory analyst signals (e.g., strong buy reiterations with large target price decreases) neutralize each other, whereas confirmatory signals reinforce each other. Further, our analysis reveals that large target price downgrades can be explained by preceding stock price decreases. However, upgrades are not preceded by stock price increases, thereby demonstrating asymmetric analyst behavior when adjusting target prices to stock prices. Our results suggest that investors should treat recommendations with caution when they are issued with large contradictory target price changes. Thus, instead of blindly following a recommendation, investors might put more weight on the change in the corresponding target price and consider transaction costs.
Keywords: Analyst recommendation; Target price; Stock performance; Trading strategy

The Relevance of Biases in Management Forecasts for Failure Prediction in Venture Capital Investments - Mokwa, Christopher Frederik; Sievers, Sönke (SSRN Electronic Journal)
This study shows how venture capital investors can identify potential biases in multi-year management forecasts before an investment decision and derive significantly more accurate failure predictions. By advancing a cross-sectional projection method developed by prior research and using firm-specific information in financial statements and business plans, we derive benchmarks for management revenue forecasts. With these benchmarks, we estimate forecast errors as an a priori measure of biased expectations. Using this measure for our proprietary dataset on venture-backed start-ups in Germany, we find evidence of substantial upward forecast biases. We uncover that firms with large forecast errors fail significantly more often than do less biased entrepreneurs in years following the investment. Overall, our results highlight the implications of excessive optimism and overconfidence in entrepreneurial environments and emphasize the relevance of accounting information and business plans for venture capital investment decisions.
Keywords: Management forecast biases; cross-sectional projection models; venture-backed start-ups; failure prediction; overoptimism; overconfidence

Biases in Management Forecasts of Venture-Backed Start-Ups: Evidence from Internal Due Diligence Documents of VC Investors - Mokwa, Christopher; Sievers, Sönke (SSRN Electronic Journal)
This study provides evidence of significant biases in multi-year management forecasts by analyzing a proprietary dataset on venture-backed start-ups in Germany. We find that revenues and expenses are highly overestimated in each of the investigated one- to five-year-ahead planning periods. Furthermore, entrepreneurs underestimate one-year-ahead profit forecasts but clearly overestimate their profit forecasts for all longer-term forecast horizons. Additional analyses reveal that teams with prior management experience issue even more overestimated forecasts and misrepresent their forward-looking information. In contrast, greater asset verifiability and corporate lead investors are associated with lower levels of forecast errors. All key results hold if bias is either measured by traditionally comparing forecasts to ex-post realizations or by using a cross-sectional projection approach based on historical accounting data developed by prior research.
Keywords: Management forecasts; Forecasting biases; Venture-backed start-ups; Projection methods

Add-On Premiums Increase Price Transparency: More Policy Holders Switch Health Plans - Schmitz, Hendrik; Eibich, P.; Ziebarth, N.R. (DIW Economic Bulletin)

Regionale Unterschiede in der stationären Versorgung: Das ländliche Krankenhaus im Fokus - Schmitz, Hendrik; Augurzky, B.; Beivers, A. (Krankenhaus-Report 2012)

Determinanten des Employer Branding in deutschen Unternehmen: Ein neoinstitutionalistischer Erklärungsansatz. - Baum, M; Gsell, L; Kabst, Rüdiger (Die Betriebswirtschaft (ZfB).)

Die Wirkung von informellen und internetbasierten Rekrutierungskanälen auf den Rekrutierungserfolg: Eine empirische Analyse in kleinen und mittleren Unternehmen. - Baum, M; Kabst, Rüdiger (Zeitschrift für Betriebswirtschaft (ZfB).)

Asset Specificity and Foreign Market Entry Mode Choice of Small and Medium-Sized Enterprises: The Moderating Influence of Knowledge Safeguards and Institutional Safeguards. - Maekelburger, B; Schwens, C; Kabst, Rüdiger (Journal of International Business Studies (JIBS).)

Der Einfluss von Rekrutiererverhaltensweisen auf den Bewerber: Ein mediierter Prozess. - Eberz, L M; Baum, M; Kabst, Rüdiger (Zeitschrift für Personalforschung (ZfP).)

Der Personalverantwortliche als strategischer Partner: Persönliche Einstellung oder subjektive Norm? - Wehner, M C; Kabst, Rüdiger; Meifert, M; Cunz, L M (Zeitschrift für Betriebswirtschaft (ZfB).)

Evaluating Major Human Resource Information Systems Design Characteristics: An Empirical Analysis. - Strohmeier, S; Kabst, Rüdiger (International Journal of Business Information Systems (IJBIS).)

Evidence-based entrepreneurship (EBE): Cumulative science, action principles, and bridging the gap between science and practice. - Frese, M; Bausch, A; Schmidt, P; Rauch, A; Kabst, Rüdiger (Foundations and Trends in Entrepreneurship.)

Graduates’ Reactions to Recruitment Process Outsourcing: A Scenario-Based Study. - Wehner, M C; Giardini, A; Kabst, Rüdiger (Human Resource Management.)

Greenfield Investment versus Akquisition: Der moderierende Einfluss wahrgenommener institutioneller Unsicherheit bei der Internationalisierung von KMU. - Eiche, J; Schwens, C; Kabst, Rüdiger (Zeitschrift für Betriebswirtschaft (ZfB).)

Internationaler Joint Venture Erfolg: Eine Meta-Analyse. - Isidor, R; Schwens, C; Kabst, Rüdiger; Hornung, F (Zeitschrift für Betriebswirtschaft (ZfB).)

Testing the Circular Structure of Human Values: A Meta-Analytical Structural Equation Modelling Approach. - Steinmetz, Holger; Isidor, R; Bäuerle, N (Survey Research Methods)

A Fuzzy Decision Support Model for Natural Disaster Response under Informational Uncertainty - Wex, Felix; Schryen, Guido; Neumann, Dirk (International Journal of Information Systems for Crisis Response and Management)

Operational Emergency Response under Informational Uncertainty: A Fuzzy Optimization Model for Scheduling and Allocating Rescue Units - Wex, Felix; Schryen, Guido; Neumann, Dirk (International Conference on Information Systems for Crisis Response and Management (ISCRAM) 2012)

IS Design Thinking in Disaster Management Research - Schryen, Guido; Wex, Felix (45th Hawaii International Conference on System Sciences)

Profis im Netz: Soziale Netzwerke könnten in Unternehmen viel mehr Nutzen stiften - woran hakt es?, in: Die Zeit (12.04.2012) - Schryen, Guido (Die Zeit)

Soziale Netzwerke in Unternehmenskontexten - Potentiale und Anforderungen, in: Information Management & Consulting, to appear - Schryen, Guido (IM Information Management & Consulting)

Berufsorientierung im Übergang - Überlegungen zur curricularen Gestaltung der Bildungsarbeit im Übergangssystem - Kremer, H.-Hugo (Individuelle Förderung und berufliche Orientierung im berufsschulischen Übergangssystem - Ergebnisse aus dem Forschungs- und Entwicklungsprojekt InLab)

Funktionen und Erträge pädagogischer Diagnostik im wirtschafts- und berufspädagogischen Bereich (Editorial) - Tramm, T.; Seeber, S.; Kremer, H.-Hugo (bwp@ Berufs- und Wirtschaftspädagogik - online)

Akademisierung der Berufsbildung - Editorial - Büchter, K.; Frommberger, D.; Kremer, H.-Hugo (bwp@ Berufs- und Wirtschaftspädagogik - online)

Open Societal Innovation: The Alemannic Definition - von Lucke, Jörn; Herzberg, Johann; Kluge, Ulrike; vom Brocke, Jan; Müller, Oliver; Zimmermann, Hans-Dieter (SSRN Electronic Journal)

Business activity management for service networks in cloud environments - Janiesch, Christian; Fischer, Robin; Matzner, Martin; Müller, Oliver (Workshop on Middleware for Service Oriented Computing)

mLearning. Akzeptanz von Mobile Learning. Chancen und Probleme in der betrieblichen Bildung - Beutner, Marc; Pechuel, R. (Jahrbuch eLearning und Wissensmanagement 2013. Die Zukunft der Bildung und die Rolle der digitalen Medien)

Sympathy or strategy: social capital drivers for collaborative contributions to the IS community - Trier, Matthias; Molka-Danielsen, Judith (European Journal of Information Systems)

Blogs as Objects of Preservation: Advancing the Discussion on Significant Properties - Stepanyan, Karen; Gkotsis, George; Kalb, Hendrik; Kim, Yunhyong; Cristea, Alexandra I.; Joy, Mike; Trier, Matthias; Ross, Seamus (iPress 2012)
challenge for the digital preservation community. While the methodological frameworks for selecting these properties provide a good foundation, a continued discussion is necessary for further clarifying and improving the available methods. This paper advances earlier work by building on the existing InSPECT framework and improving its capabilities of working with complex/compound objects like blogs. The modifications enable a more thorough analysis of object structures, accentuate the differences and similarities between the framework’s two streams of analysis (i.e. Object and Stakeholder analysis) and, subsequently, improve the final reformulation of the properties. To demonstrate the applicability of the modified framework, thepaper presents a use case of a blog preservation initiative that is informed by stakeholder interviews and evaluation of structural and technological foundations of blogs. It concludes by discussing the limitations of the approach and suggesting directions for future research.
Keywords: Blogs; Weblogs; Digital Preservation; Significant Properties

Sentiment Polarization and Balance among Users in Online Social Networks - Hillmann, Robert; Trier, Matthias (AMCIS 2012 Proceedings)
Communication within online social network applications enables users to express and share sentiments electronically. Existing studies examined the existence or distribution of sentiments in online communication at a general level or in small-observed groups. Our paper extends this research by analyzing sentiment exchange within social networks from an ego-network perspective. We draw from research on social influence and social attachment to develop theories of node polarization, balance effects and sentiment mirroring within communication dyads. Our empirical analysis covers a multitude of social networks in which the sentiment valence of all messages was determined. Subsequently we studied ego-networks of focal actors (ego) and their immediate contacts. Results support our theories and indicate that actors develop polarized sentiments towards individual peers but keep sentiment in balance on the ego-network level. Further, pairs of nodes tend to establish similar attitudes towards each other leading to stable and polarized positive or negative relationships
Keywords: Social Network Analysis; Ego-Network Analysis; Node Polarization; Sentiment Dissemination

The Blogosphere as Oeuvre: Individual and Collective Influence on Bloggers - Kalb, Hendrik; Trier, Matthias (ECIS 2012 Proceedings)
Blogging has often been described as writing an online diary but, nowadays, it is more diverse and a considerable amount of blogs forms a common interconnected resource – the blogosphere – with comprehensive societal impact. While various studies have inquired social-psychological influenceson the intention to contribute to an individual blog, the perceptions related to creating such a common valuable good have not yet been focussed. Therefore, we introduce a new construct – the oeuvre of blogging – to better account for the notion of the blogosphere as a collective outcome. Furthermore, we propose a research model to inquire the influence of individual and collective beliefs on the oeuvre in comparison to short-term blogging activity. We conducted an online survey with 509 international distributed bloggers to test our model. The results of our study provide support for the importance of an oeuvre construct to explain influences on bloggers and blogging
Keywords: Blog; Blogosphere; Collective benefit; PLS; Knowledge sharing

Dissemination Patterns and Associated Network Effects of Sentiments in Social Networks - Hillmann, Robert; Trier, Matthias (Proceedings of the 2012 IEEE/ACM International Conference on Advances in Social Networks Analysis and Mining)
Communication in online social networks has been analyzed for some time regarding the expression of sentiments. So far, very little is known about the relationship between sentiments and network emergence, dissemination patternsand possible differences between positive and negative sentiments. The dissemination patterns analyzed in this study consist of network motifs based on triples of actors and the ties among them. These motifs are associated with common social network effects to derive meaningful insights about dissemination activities. The data basis includes several thousand social networks with textual messages classified according to embedded positive and negative sentiments. Based on this data, sub-networks are extracted and analyzed with a dynamic network motif analysis to determine dissemination patterns and associated network effects. Results indicate that the emergence of digital social networks exhibits a strong tendency towards reciprocity, followed by the dominance ofhierarchy as an intermediate step leading to social clustering with hubs and transitivity effects for both positive and negative sentiments to the same extend. Sentiments embedded in exchanged textual messages do only play a secondary role in network emergence and do not express differences regarding the emergence of network patterns.
Keywords: Social Network Analysis; Dynamic Network Motif Analysis; Sentiment Dissemination; Networking Effects; Triads

More health care utilization with more insurance coverage? Evidence from a latent class model with German data - Schmitz, Hendrik (Applied Economics)

Zufriedenheit der Studierenden mit den Serviceeinrichtungen einer Universität: Ergebnisse einer explorativen multivariaten Analyse - Blum, Mareike; Kraft, Manfred; Lück, Sonja (Hochschulmanagement)

Coalitional and Strategic Market Games - Brangewitz, Sonja

An Automatic Approach for Parameter Optimization of Material Flow Simulation Models based on Particle Swarm Optimization - Laroque, Christoph; Pater, Jan-Patrick
The analysis of production systems by the use of discrete, event-based simulation is widely used and accepted as decision support method. It aims either at the comparison of competitive designs or the identification of a “best possible” configuration of the simulation model. Here, combinatorial techniques of simulation and optimization methods support the user in finding optimal solutions, which typically result in long computation times and though often prohibit a practical application in today’s industry. This paper presents a fast converging procedure as a combination of a swarm heuristic, namely the particle swarm optimization, and the material flow simulation to close this gap. Faster convergence is realized by a specific extension of classic PSO implementations. First results show the applicability with a simulation reference model.

Multi-Layer Architecture for Transition of Business-Models to common Software-Tools and Optimization of the Model-Structure exemplified with Microsoft SharePoint 2010 - Lauck, Sebastian; Hartmann, Philip; Laroque, Christoph

Fast Converging, Automated Experiment Runs for Material Flow Simulations Using Distributed Computing and Combined Metaheuristics - Laroque, Christoph; Klaas, Alexander; Fischer, Jan-Hendrik; Kuntze, Mathis (Proceedings of the 2012 Winter Simulation Conference)

Application relevance of dissertations - Dangelmaier, Wilhelm

Bi-objective-optimisation of an international transportation problem for CO2-efficient schedules - Kl{\, Benjamin; Pater, Jan-Patrick; Irohara, Takashi; Xue, Yudong (International Journal of Engineering Management and Economic)
The transportation sector accounts for a considerable portion of global CO2 emissions and the demand for transport, especially for international transport, is increasing. Current approaches to reduce CO2 emission on an operational level ignore time-related objectives and focus on simultaneous optimisation of economic and ecological objectives. In general, considering the minimisation of CO2 emissions in transportation scheduling introduces a trade-off between economic and ecological concerns. The concept of eco-efficiency is important in order to evaluate the economical value and ecological quality of business decisions. Nevertheless, this concept has primarily been applied to strategic decisions. In the present paper we demonstrate the applicability of this concept to operative decisions and introduce a bi-objective evolutionary optimisation approach for the approximation of CO2-efficient schedules in an international transportation problem.

Visualization and Collaborative Editing of Simulation Models With Heterogeneous Clients - Implemented Into the Simulator d3fact - Renken, Hendrik; Eichert, Felix Alexander; Brandt, Sascha; Klaas, Alexander

Development of cost-effective spare parts logistics for a solar technology provider under monet {\ "a} rer Ber ü consideration of resulting CO2 emissions - Dangelmaier, Wilhelm; Laroque, Christoph; Delius, Robin; Streichhan, Jenny

Kontinuierliche Adaption von Lieferketten durch Leistungsbewertung und -steuerung dynamischer Geschäftsprozesse - Hartmann, Philip; Laroque, Christoph

Comparing a hybrid simulation & optimization approach with a purely stochastic optimization to increase the robustness of production plans - Fischer, Jan-Hendrik; Delius, Robin; Horstkemper, Dennis; Laroque, Christoph

Increase of robustness in production plans using a hybrid optimization and simulation approach - Laroque, Christoph; Delius, Robin; Fischer, Jan-Hendrik (International Journal on Advances in Systems and measurements)

Parallel scheduling for evolving manufacturing systems - Klöpper, Benjamin; Pater, Jan-Patrick; Dangelmaier, Wilhelm (Proceedings of the 9th IEEE International Conference on Industrial Informatics)

Building blocks of business informatics - basics and applications - Fischer, J; Dangelmaier, Wilhelm; Nastansky, Ludwig; Suhl, L

Robust solution approach to an uncertain CLSP problem - Kaganova, Ekaterina (Applied Mathematical Optimization and Modelling)

A multi-objective evolutionary approach to scheduling for evolving manufacturing systems - Kl{\, Benjamin; Pater, Jan-Patrick; Honiden, Shinichi; Dangelmaier, Wilhelm (Evolving Systems)
Persistent trends like quickly changing production programs, increasing customer individual manufacturing and Sustainable Manufacturing create complex systems of objectives in manufacturing control. Service-oriented manufacturing systems and self-optimizing manufacturing resources offer the required flexibility to consider these objectives in accordance with the current organizational and economical situation. On the downside, this increase in flexibility make the control of manufacturing systems more difficult and presents new challenges regarding the scheduling. To meet these challenges, we developed scheduling framework that supports alternative process plans and considers the internal states trajectories of resources. In order to support the user in a complex decision-making environment, evolutionary multi-objective optimization is used to generate a set of relevant schedules and an interface to select the most appropriate schedule is provided.

Cascaded Heterogeneous Simulations for Analysis of Mechatronic Systems in Large Scale Transportation Scenarios - Hassan, Bassem; Wassmann, Helene; Klaas, Alexander; Kessler, Jan Henning (Proceedings of the 2012 Emerging M&S Applications in Industry & Academia Symposium, Spring Simulation Multiconference,)

Ensuring calls to automotive suppliers with minimal costs with special consideration of liquidity {\ "a} ts-, Besch {\ "a} qualification, know-how and IT restrictions - Delius, Robin

A Cross-Level Approach To Planning Changeability in Distribution Systems - Klingebiel, Katja; Winkler, Matthes; Klaas, Alexander; Laroque, Christoph (Proceedings of the 2012 Emerging M&S Applications in Industry & Academia Symposium, Spring Simulation Multiconference)

Effektives Customer Relationship Management: Instrumente - Einführungskonzepte - Organisation - Helmke, Stefan, Stefan; Uebel, Matthias; Dangelmaier, Wilhelm

Credit risk securitization and bank soundness: Evidence from the microlevel for Europe - Michalak, Tobias C.; Uhde, André (Quarterly Review of Economics and Finance)
Using a unique sample of 749 cash and synthetic securitization transactions issued by 60 stock-listed bank holdings in the EU-13 plus Switzerland over the period from 1997 to 2007 this paper provides empirical evidence that credit risk securitization has a negative impact on the issuing banks’ financial soundness. Baseline findings hold even when controlling for likely reverse causality by employing instrumental variable techniques and substituting the accounting-based z-score ratio by market-based indicators of bank risk. Moreover, investigating the relationship between credit risk securitization and single z-score components in order to evaluate significant transmission channels proposed by relevant theoretical literature, we find a negative impact of securitization on bank profitability and capital environment as well as a positive relationship between securitization and the issuing bank's return volatility. Against the background of our empirical results we underline that the decision by the Basel Committee to enhance the new Basel III framework in the field of securitization is a step in the right direction.
Keywords: Credit risk securitization Bank soundness European banking

Cross-border bank lending - Empirical evidence on further determinants from OECD banking markets - Müller, Oliver; Uhde, André (Journal of International Financial Markets, Institutions & Money)
Employing data on foreign bank claims from 13 OECD countries on 51 emerging markets between 1993 and 2007, this study investigates specific characteristics of OECD banking markets and lending banks as new important determinants of cross-border lending. We initially provide empirical evidence that in addition to well-accepted “gravity measures”, characteristics of OECD banking markets as well as lending banks’ attributes may describe further important determinants of cross-border bank lending with regard to our sample. Building subsamples of more-developed emerging markets vs. frontier markets, addressing (non) common lender relationships and analyzing cross border lending flows during different time periods, our analysis additionally reveals that both the determinants’ explanatory power and their direction of impact notably vary with respective subsamples.
Keywords: Foreign bank claims; Gravity measures; OECD banking markets’ characteristics; Lending banks’ characteristics

Wealth effects of credit risk securitization in European Banking - Farruggio, Christian; Michalak, Tobias C.; Uhde, André (Journal of Business Finance and Accounting)
Using a unique cross‐sectional dataset of 381 cash and synthetic securitizations issued by 53 banks from the EU‐15 plus Switzerland between 1997 and 2007, this paper provides empirical evidence for time‐dependent negative wealth effects of credit risk securitization announcements in European banking. Baseline results hold when comparing estimated wealth effects with a control group of similar but non‐securitizing banks for the relevant time period. Moreover, building several sub samples we find that the nexus between credit risk securitization, the issuing banks’ overall risk exposure and wealth effects is associated with a variety of transaction‐ and bank‐specific factors.
Keywords: wealth effects; credit risk securitization; Europe; event study

Measuring the quality of banking supervision revisited - Assessments by German banks before and during the financial crisis - Paul, Stephan; Stein, Stefan; Uhde, André (Journal of Governance and Regulation)
This contribution presents and discusses main results of a new survey on the assessment of supervisory quality among German banks in 2010. In particular, it is analyzed if and how supervised banks’ perception of the quality of supervisory authorities and their instruments has changed due to the financial crisis starting in mid-2007. Subsequently, results from the recent survey are compared with findings provided by a former study carried out by the authors in 2006 (Paul, Stein and Uhde, 2008).
Keywords: banking supervision; quality; assessment; banking sector

Sovereign Risk and Bank-Specific CDS Pricing - Meine, Christian; Michalak, Tobias C.; Uhde, André
Employing time series of single-name CDS market spreads from 29 European banks located in the EU-12 plus Switzerland and the UK over the period from January 2004 through September 2010 this paper analyses the relationship between increasing sovereign risk and bank-specific CDS pricing. Results from calculating relative CDS spread deviations (model minus market spreads) initially reveal a price bubble in the European CDS market until the beginning of the financial crisis in mid-2007. From this point in time the gap narrows remarkably during the financial crisis and sovereign debt crisis period. Corresponding to these findings, the empirical analysis reveals a negative impact of sovereign risk on calculated CDS spread differentials indicating a spill-over effect between sovereign risk and bank risk and hence, a positive effect on bank-specific CDS pricing. Further analyses reveal that the perception of sovereign risk is not crisis- but country-dependent suggesting that bank-specific CDS market spreads may already include a premium to cover sovereign risk from PIIGS countries during the pre-crisis period in Europe.
Keywords: Sovereign risk; Structural credit risk models; bank-specific CDS pricing

Wertorientierte Vergütung des Aufsichtsrats - Auswirkungen auf den Unternehmenswert - Ebert, Michael; Zein, Nicole (Betriebswirtschaftliche Forschung und Praxis)

Der Einfluss der Zinsschranke auf unternehmerische Kapitalstrukturentscheidungen - Maßbaum, Alexandra; Klotzkowski, Tasja; Sureth-Sloane, Caren (Zeitschrift für Betriebswirtschaft)